Education Partnerships between Local Education Authorities and Universities: A Promising Strategy but Undeveloped - Abdul Rahman; Syamsuardi Saodi; Muhammad Irfan; Nasrah Nasrah (Yayasan Keluarga Guru Mandiri, 2022)
Education partnerships (EP) between local education authorities (LEAs) and universities including teacher training institutes (LPTK) are seen as sine qua non to improve and develop the service and quality of education. EP is one key strategy to leverage education improvement initiatives in the current education reform and decentralisation. This paper presents the description of EP that exists between Makassar State University as LPTK and all LEAs in the province of South Sulawesi as well as to see the constraints and needs for partnerships in developing and improving education services and quality at local level. A quantitative method by using survey design was employed. A total population sampling was applied to 24 LEAs in the province of South Sulawesi who completed a 21-item questionnaire regarding the research variables. LEA in general have positive perception and attitude towards the importance and power of EP in their efforts to develop and improve education in their regions. The findings reveal EP between LEAs and LPTK have existed and manifested in various education improvement activities. However, there is a discrepancy between the actual needs of LEAs and the existing activities/programs in the current EP. In conclusion, EP is a promising strategy for education improvement, but it is undeveloped in its process and implementation.